DAMPAK PERKEMBANGAN TEKNOLOGI DALAM PENDIDIKAN - Wulandari, Ratna (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2023)
Technology and information experienced rapid development in the era of the industrial revolution 4.0. Technological changes and developments have a major influence on all aspects of life. One of them is in the world of education. The use of technology affects the implementation of an all-digital-based learning process. Both teachers and students must be able to adapt to the times. Technological developments can bring positive and negative influences on the world of education. The negative impact caused will have an effect on changes in behavior, norms, rules, ethics, or morals of human life. And can conflict with the rules, ethics, norms, and morals in social life.This study aims to determine the positive and negative impacts of technological change in the world of education and efforts to overcome the negative impacts that occur.The type of research used in this study is a qualitative descriptive research with a literature study research method.Based on the results of the study it was found that technological developments in the world of education can have positive and negative influences on human life both in behavior, ethics, norms, rules, or moral life. To minimize the negative influence of technology in education, several alternative solutions are needed that can reduce this negative influence. So that we can wisely and responsibly utilize technology in all aspects of life.